The Reasons of Casual Style used By Host in Nebeng Boy - Mey Ramenawati Silalahi; Meisuri . .; Masitowarni . Siregar (LINGUISTIK TERAPAN, 2022)
ABSTRACT This article was discussed about the reasons of casual style by Boy William and Rita Ora in Nebeng Boy based on Martin Joos theory. They were frozen style, casual style, consultative style, formal style and intimate style. This article was aimed to found the reasons why the host used casual style in his vlog show. This article used Holmes theory to found that reasons. This article applied descriptive qualitative method. The data of this research were taken from the vlogshow video and the video transcript on yotube.